TERAPI HEPIKA DAN RELAKSASI BENSON UNTUK KELELAHAN PADA PASIEN ANEMIA - Tarisa Fitri, Aliffia Ananda; Purwanto, Edi (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Anemia is a hematological disorder that can cause fatigue and reduce activity tolerance as well as quality of life. The management of anemia is not limited to pharmacological therapy but also requires safe and easily applicable non-pharmacological interventions, such as the combination of HEPIKA therapy, which includes Range of Motion [ROM] exercises and Benson relaxation. This combination of interventions can help improve circulation, reduce stress, and alleviate fatigue. Objective: To determine the effect of the combination of HEPIKA therapy and Benson relaxation in reducing fatigue levels in anemia patients.To find out the factors related to exclusive breastfeeding at the Amuntai Selatan Community Health Center. Methods: This study employed a case study design with a one-subject pre–post intervention approach. The subject was a 20-year-old female with moderate anemia experiencing fatigue. The intervention, consisting of a combination of HEPIKA therapy and Benson relaxation, was administered for one week with five evaluation sessions. Fatigue levels were measured using the Fatigue Severity Scale [FSS] before and after the intervention. Results: The FSS score before the intervention was 6.1, indicating severe fatigue, and decreased to 2.0 after the intervention, indicating mild to no fatigue. Additionally, there was an improvement in activity tolerance, peripheral perfusion, stabilization of breathing patterns, and the patient’s ability to perform light activities without easily feeling fatigued. Conclusion: The combination of HEPIKA therapy and Benson relaxation is effective in reducing fatigue levels in patients with anemia within a relatively short period. This intervention has the potential to be an alternative non-pharmacological therapy to improve activity tolerance and quality of life in patients.